Semiose: O interpretante e a inferência de Charles Sanders Peirce - Lafuente, Luis Antonio Mopi (2016)
This research has as object of study the relation between interpretant and inference in the semiotic theory of the American thinker Charles Sanders Peirce, and as method of working it was used the bibliographic research and interpretation of the concepts of interpretant and inference, in addition of the analysis of some examples where one can observe in an “empirical” way the action of those concepts. Among the main results we can mention the fact that to study the relation between inference and interpretant in Peirce‟s thought means analyzing how the sign arises, grows, and corrects itself following an intention or norm contained in a specific kind of interpretant (the final interpretant), intention or norm that one can resume in the sign‟s tendency to represent its object in all possible aspects. It was also found that the logical foundations of the interpretant reside in the concept of logical causation, since the interpretant is the mediate result of the object‟s action through sign; that is the reason why the representation is considered as the orderly form of a logical process that occurs among the three elements of Peirce‟s sign (representamen-object-interpretant). That is why it can say that one of the first functions of the interpretant is to provide the inference “such sign represents such object”, point of origin of any sign, and therefore of any language, and over which any posterior interpretation is based. In fact, the sign‟s inferential origin is one of the foundations of Peirce‟s anti-Cartesian epistemology, which denies the intuitive bases of the science and thought of his time; for Peirce there is no immediate cognition (intuition) of the object because any knowledge is mediated by the sign and previous knowledge. The inferential bases of the Percean epistemology stand in the mathematical concept of continuum, idea that in the general framework of Peirce‟s evolutionary philosophy is known under the name of synechism theory. Thereby the cognition as inferential process presupposes as logically possible a regression to infinity toward the object since the meaning of a sign is another sign, and a progression to infinity toward the final interpretant, since any sign is interpreted in a subsequent sign. On these theoretical bases one can conclude that the being of the sign consists in to exist as a logical entity.